2019
DOI: 10.3390/ijms20092211
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cobalt Protoporphyrin IX and Tricarbonyldichlororuthenium (II) Dimer Treatments and Its Interaction with Nitric Oxide in the Locus Coeruleus of Mice with Peripheral Inflammation

Abstract: Heme oxygenase 1 (HO-1) and carbon monoxide were shown to normalize oxidative stress and inflammatory reactions induced by neuropathic pain in the central nervous system, but their effects in the locus coeruleus (LC) of animals with peripheral inflammation and their interaction with nitric oxide are unknown. In wild-type (WT) and knockout mice for neuronal (NOS1-KO) or inducible (NOS2-KO) nitric oxide synthases with inflammatory pain induced by complete Freund’s adjuvant (CFA), we assessed: (1) antinociceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…CoPP activates the expression of HO-1 in the paws, 14 dorsal root ganglia, 48 and loci coeruleus of animals with peripheral inflammatory pain. 16 In summary, these data reveal that the peripheral and central protective roles played by CORM-2 and CoPP during chronic pain are mainly mediated by HO-1 activation ( Figure 2).…”
Section: Mechanisms Of Action Of Ho-1 and Carbon Monoxide During Chmentioning
confidence: 70%
See 3 more Smart Citations
“…CoPP activates the expression of HO-1 in the paws, 14 dorsal root ganglia, 48 and loci coeruleus of animals with peripheral inflammatory pain. 16 In summary, these data reveal that the peripheral and central protective roles played by CORM-2 and CoPP during chronic pain are mainly mediated by HO-1 activation ( Figure 2).…”
Section: Mechanisms Of Action Of Ho-1 and Carbon Monoxide During Chmentioning
confidence: 70%
“…15,[79][80][81][82] Accordingly, the expression of NOS1 and/or NOS2 is upregulated in the dorsal root ganglia, spinal cords, and loci coeruleus of animals with peripheral inflammation. 16,[83][84][85][86] Moreover, hypersensitivity induced by peripheral inflammation is significantly diminished in NOS1-KO and NOS2-KO animals and is reversed by the administration of selective nitric oxide synthase inhibitors. 79,82,83 Interestingly, the systemic administration of CORM-2 and CoPP normalizes the upregulation of NOS1 induced by peripheral inflammation in the dorsal root ganglia and locus coeruleus.…”
Section: Mechanisms Of Action Of Ho-1 and Carbon Monoxide During Chmentioning
confidence: 99%
See 2 more Smart Citations
“…Data obtained by Sorrenti et al, demonstrated that inducible nitric oxide synthase/gamma-Glutamyl-cysteine ligase (iNOS/GGCL) and dimethylarginine dimethylaminohydrolase (DDAH) dysregulation may play a key role in high glucose mediated oxidative stress, whereas HO-1 inducers such as Caffeic acid phenethyl ester (CAPE) or its more potent derivatives may be useful in diabetes and other stress-induced pathological conditions [13]. The study of Moreno et al reveals an interaction between HO-1 and nitric oxide synthase-1 (NOS1)/ nitric oxide synthase-2 (NOS2) during peripheral inflammation and shows that Cobalt protoporphyrin (CoPP) and CO-releasing molecules-2 (CORM-2) improved HO-1 expression and modulated the inflammatory and/or plasticity changes caused by peripheral inflammation in the locus coeruleus [14].…”
mentioning
confidence: 99%